Sequence heterogeneity of nSSR and cpDNA loci of Cucurbits (Citrullus sp.) - Tóth, Zoltán; Gyulai, Gábor; Szabó, Zoltán; Horváth, Lajos; Gyulai, Ferenc; Heszky, László (Acta Agraria Debreceniensis, 2007)
The evolution of water melon (Citrullus lanatus) microsatellites from the 15th century (Debrecen); 13th (Buda); and 18th century, (Pannonhalma) were analyzed. Microsatellite (nSSR, nuclear simple sequence repeat) and cpDNA profiles of the aDNA (ancient DNA) of seed remains were compared to modern water melon cultivars and landraces. Sixteen primer pairs were applied. Sequence analysis at the (CT)26 and cpDNA trnV loci revealed a (CT)3 and Adenin deletions, respectively, form the current water melon cultivar compared to the medieval sample. Cila-1), a new LTR retrotansposon has been described. For morphological reconstruction, a dendrogram produced by SPSS11 based on the presence versus absence of 24 phenotypic characters were also analyzed.